Mechanistic Study of Ir(III) Catalyzed Oxidation of Amines by Acidic Solution of Potassium Bromate - Singh, R.A.; Kumar Singh, Ashish; Pandey, K.; Jaiswal, Jaya; Singh, Kamini (Asian Journal of Chemistry, 2010)
Kinetics and mechanism of Ir(III) catalyzed oxidation of methyl amine (MA) and ethyl amine (EA) by KBrO3 in acidic medium have been investigated. Zero-order dependence in [KBrO3] was observed, while first-order with respect to both methyl amine and ethyl amine and Ir(III) was observed. Variation of ionic strength (μ) of the medium and addition of Hg(OAc)2 (used as Br– scavenger) had an insignificant effect on the rate of the reaction. Positive effect of addition of [Cl–] on the rate of reaction were observed. A suitable mechanism consistent with the observed kinetic data has been suggested and related rate law deduced.